A Case Study on the Role of Chief Integrity Officer (CIO) as a Control Mechanism in Malaysian Public Sector Organizations - Ishak, Ismail; Hasnah, Haron; Asmawati, Sajari (2016)
The purpose of this paper is to explain the role of Chief Integrity Unit (CIU) as a control mechanism in the governance of Malaysian public sector organizations. Malaysian Government Transformation Program (GTP) has triggered the establishment of Integrity Unit in all public sector entities with aim of fighting corruption. Thus, this study specifically focuses on the role of CIU in influencing the level of ethics and integrity in the organizations which eventually gives impact on the practices of management accounting. There are two different types of public sector entities that have been studied i.e., state level (CSA) and state statutory body (CSB). An explanatory case study method is used to collect the data whereby semi structured interviews, informal conversations, questionnaire and document reviews are conducted. The finding shows that CIU plays a crucial role in shaping the ethical and integrity culture within the organization. The overall score of the level of ethics and integrity for both case studies is more than 50 per cent which indicates that both CSA and CSB are serious in initiating proper integrity mechanism into their daily activities at work places to maintain the highest levels of transparency, integrity and professionalism. CSB shows a higher percentage as compared to CSA that are 70.85% and 68.26% respectively. CSB performed better than CSA in almost all dimensions except for dimensions of Leadership, Confidential Advice and Support, and Ethics Communication where CSA scores higher percentage. Therefore, it is highly recommended that CSB focus more on these three dimensions and vice versa to CSA. Further in depth study is highly recommended to get more generalize results on the role of Chief Integrity Unit (CIU) as a control mechanism in upholding good governance of Malaysian public sector organizations especially through enhancement of management accounting.